Differences in molecular epidemiology of lung cancer among ethnicities (Asian vs. Caucasian) - Izumi, Motohiro (J Thorac Dis, 2020)
BACKGROUND: Differences in carcinogenesis and therapeutic efficacy according to ethnicity have been reported for lung cancer, and understanding differences in genetic mutation profiles among ethnicities is important for interpreting the results of clinical trials, preventing carcinogenesis, and individualizing treatment. However, no studies have focused on differences in mutation profiles among different ethnicities using large-scale genomic analysis data with detailed information on smoking history, the main cause of lung cancer. METHODS: To clarify the differences in genetic mutation profiles between Caucasian and Japanese subjects, we compared data from The Cancer Genome Atlas, which mainly included Caucasians, with results from the Japan Molecular Epidemiology for lung cancer study, which is an epidemiological study only involving Japanese subjects. We divided the participants into four groups according to smoking status and performed comparative analysis by tissue type (lung adenocarcinoma and squamous cell lung cancer). RESULTS: In patients with lung adenocarcinoma, the frequency of EGFR mutations was lower in Caucasian subjects than in Japanese subjects (14.6% vs. 51.1%), whereas the frequencies of mutations in other genes, namely KRAS (32.9% vs. 9.3%), TP53 (45.2% vs. 20.7%), BRAF (9.6% vs. 1.3%), PIK3CA (5.9% vs. 2.6%), KEAP1 (17.8% vs. 0.5%), NF1 (10.9% vs. 0.5%), STK11 (17.8% vs. 0.7%), RBM10 (8.7% vs. 0.1%), and MET (7.8% vs. 0.1%), were higher in Caucasian subjects. Among patients with squamous cell carcinoma, TP53 (81.2% vs. 49.1%), PIK3CA (14.5% vs. 6.8%), KEAP1 (12.7% vs. 0.9%), and NFE2L2 mutations (15.8% vs. 13.6%) were more common in Caucasian subjects. CONCLUSIONS: Ethnicity is an important and complex characteristic that must be recognized and considered, even in the era of precision medicine. We should collaborate to share data for different ethnicities and incorporate them into clinical practice and the design of global clinical studies. Carefully designed molecular epidemiological studies focusing on ethnic differences are warranted.